A laboratory course in tissue engineering - Micou, Melissa Kurtis; Kilkenny, Dawn M. (Boca Raton : Taylor & Francis, 2013)
"This book is a hands-on lab manual for tissue engineering (TE) instruction. The manual contains classic TE experiments as well as modern TE techniques, emphasizing the importance of engineering analysis, mathematical modeling, and statistical design of experiments. It includes over 20 stand-alone experiments that provide more than a semester's worth of activities, allowing instructors to customize their courses. The authors present experiments that use equipment commonly found in labs equipped for tissue culture, and they include pre-lab and discussion questions for each experiment"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Tissue Engineering -- Laboratory Manuals